2017
DOI: 10.1038/onc.2017.327
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Mucin Muc4 promotes blood cell association with tumor cells and mediates efficient metastasis in a mouse model of breast cancer

Abstract: Mucin-4 (Muc4) is a large cell surface glycoprotein implicated in the protection and lubrication of epithelial structures. Previous studies suggest that aberrantly expressed Muc4 can influence the adhesiveness, proliferation, viability and invasiveness of cultured tumor cells, as well as the growth rate and metastatic efficiency of xenografted tumors. While it has been suggested that one of the major mechanisms by which Muc4 potentiates tumor progression is via its engagement of the ErbB2/HER2 receptor tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…10). Notably we identified mutations within Mucin 4 ( Muc4 ), which are potentially impactful due to Muc4 ’s emerging roles in Her2-positive cancer and metastasis 25 . Interestingly, we observed that PyMT-induced tumors had more SNVs in the coding regions of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…10). Notably we identified mutations within Mucin 4 ( Muc4 ), which are potentially impactful due to Muc4 ’s emerging roles in Her2-positive cancer and metastasis 25 . Interestingly, we observed that PyMT-induced tumors had more SNVs in the coding regions of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the MMTV-Neu model had no genes with shared mutations in all samples and only five genes containing a coding, non-synonymous mutation in more than one sample ( Figure S6). Notably we identified mutations within Mucin 4 (Muc4) which are potentially impactful due to Muc4's emerging roles in Her2 positive cancer and metastasis 16 . Interestingly, we observed that PyMT induced tumors had more SNVs in the coding regions of the genome.…”
Section: Main Textmentioning
confidence: 99%
“…Another two molecules involved in WDTC progression were also related to cancer cell stemness. As reported in ovarian carcinoma (45), MUC4 can induce epithelial-mesenchymal transition, and it can enhance the invasion of tumors in pancreatic and breast cancers (46,47). miR-30a-5p, the only overlapped miRNA in metastatic lesions, is reported to be associated with cancer metastasis.…”
Section: Discussionmentioning
confidence: 76%